The effect of adenosine monophosphate deaminase overexpression on the accumulation of umami-related metabolites in tomatoes - Chew, Bee Lynn; Fisk, Ian D.; Fray, Rupert; Tucker, Gregory A.; Bodi, Zsuzsanna; Ferguson, Alison; Xiao, Wei; Seymour, Graham B. (Springer, 2016)
Taste is perceived as one of a combination of five sensations, sweet, sour, bitter, salty, and umami. The umami taste is best known as a savoury sensation and plays a central role in food flavour, palatability, and eating satisfaction. Umami flavour can be imparted by the presence of glutamate and is greatly enhanced by the addition of ribonucleotides, such as inosine monophosphate (IMP) and guanosine monophosphate (GMP). The production of IMP is regulated by the enzyme adenosine monophosphate (AMP) deaminase which functions to convert AMP into IMP. We have generated transgenic tomato (Solanum lycopersicum) lines over expressing AMP deaminase under the control of a fruit-specific promoter. The transgenic lines showed substantially enhanced levels of AMP deaminase expression in comparison to the wild-type control. Elevated AMP deaminase levels resulted in the reduced accumulation of glutamate and increased levels of the umami nucleotide GMP. AMP concentrations were unchanged. The effects on the levels of glutamate and GMP were unexpected and are discussed in relation to the metabolite flux within this pathway.